APPENDICITIS PRESENTATION VARIABILITY IN LOW-SOCIOECONOMIC POPULATIONS: EXAMINE IF AND HOW THE TYPICAL CLINICAL PRESENTATION DIFFERS IN UNDERSERVED POPULATIONS, FOCUSING ON DIAGNOSTIC DELAYS AND OUTCOMES (The Research of Medical Science Review, 2024)
Introduction: Appendicitis is one of the most prevalent abdominal emergencies globally, requiring timely medical intervention to prevent complications such as perforation, sepsis, and even death. Objective: The main objective of the study is to find the appendicitis presentation variability in low-socioeconomic populations and examine if and how the typical clinical presentation differs in underserved populations, focusing on diagnostic delays and outcomes. Methodology: This retrospective observational study was conducted at Bolan Medical College Quetta during June 2024 till September 2024. Data were collected from 210 patients. Patient data were collected from electronic medical records (EMRs) and physical charts with permission from the respective healthcare institutions. Information was anonymized to protect patient privacy. Results: Data were collected from 210 patients from low socioeconomic status with more prevalent in males (57%) compared to females (43%), with the majority of cases (60%) occurring in the 15–40 years age group. Children under 15 years accounted for 25% of cases, while individuals over 40 comprised 15%. Typical symptoms, such as right lower quadrant pain and fever, were observed in 67% of patients, whereas 33% presented with atypical symptoms, including generalized pain (21%), urinary symptoms (7%), and mild or absent fever (5%). Diagnostic methods showed varying accuracy, with clinical examination being utilized in 110 cases (75% accuracy), while imaging modalities like ultrasound and CT scans improved diagnostic precision, achieving accuracies of 85% and 95%, respectively. Conclusion: It is concluded that socioeconomic factors significantly influence the presentation, diagnosis, and management of appendicitis in low-socioeconomic populations. Delayed diagnosis, limited access to healthcare, and atypical symptom presentation contribute to higher complication rates and prolonged recovery.1. RLQ - Right Lower Quadrant 2. LQ - Lower Quadrant 3. LSP - Low Socioeconomic Population 4. CT - Computed Tomography 5. EMRs - Electronic Medical Records 6. SPSS - Statistical Package for the Social Sciences 7. ALC - Advanced Low-Cost 8. LLC - Low-Literacy Cost LMICs - Low- and Middle-Income Countries